Challenges in the crystal growth of Li2CuO2 and LiMnPO4 - Wizent, Nadja; Behr, Günter; Löser, Wolfgang; Büchner, Bernd; Klingeler, Rüdiger (Journal of crystal growth, 2011)
Single crystals of a potential battery material, LiMnPO4, and the spin ladder compound Li2CuO2 are grown under elevated gas pressure in a newly designed vertical floating zone facility with optical heating. Lithium vaporization and its reaction with gases in the growth chamber are principal challenges of the growth process. By applying high argon pressure of 40bar during Travelling Solvent Floating Zone growth of LiMnPO4 the vaporization was reduced by orders of magnitude. The optical radiation, penetrating the transparent melt, affects the crystal/melt interface curvature during the growth. The growth direction was recognized to be decisive for changing the interface curvature from concave to convex and enabling efficient grain selection. By using an Ar/O2 gas mixture in crystal growth of Li2CuO2 the direct exchange between oxygen in the atmosphere and the floating zone, the oxygen content of the melt and finally the quality of Li2CuO2 crystals are controlled.